2011
DOI: 10.1111/j.1528-1167.2011.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and volumetric abnormalities of the putamen in juvenile myoclonic epilepsy

Abstract: and zDepartment of Radiology, University of Mü nster, Mü nster, Germany SUMMARY Purpose: Patients with juvenile myoclonic epilepsy (JME) show evidence of microstructural white matter (WM) damage of thalamocortical fiber tracts and changes of blood oxygen level dependent (BOLD) signal in a striatothalamocortical network. The objective of the present study was to investigate microstructural and volumetric alterations of the putamen in patients with JME using diffusion tensor imaging (DTI) and conventional magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 54 publications
12
84
0
1
Order By: Relevance
“…This is consistent with findings of prior studies that focused on microstructural abnormalities in the internal capsule [6,16,17,22]; however, this is the first study showing a clear mean FA reduction in the Table 2 Eta values of clinical parameters ARAS LGN GIC ICP VMT L R L R L R L R FA MD FA MD FA MD FA MD FA MD FA MD FA MD FA MD GIC in pPPR JME patients in contrast to the nPPR group when compared to healthy controls. The GIC predominantly contains motor fibers between the thalamus and the premotor cortex including the supplementary motor area [26].…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with findings of prior studies that focused on microstructural abnormalities in the internal capsule [6,16,17,22]; however, this is the first study showing a clear mean FA reduction in the Table 2 Eta values of clinical parameters ARAS LGN GIC ICP VMT L R L R L R L R FA MD FA MD FA MD FA MD FA MD FA MD FA MD FA MD GIC in pPPR JME patients in contrast to the nPPR group when compared to healthy controls. The GIC predominantly contains motor fibers between the thalamus and the premotor cortex including the supplementary motor area [26].…”
Section: Discussionsupporting
confidence: 93%
“…In addition to changes in the hippocampus, they also observed the significantly reduced volumes of the left thalamus, left caudate nucleus and bilateral lenticular nuclei [27]. Consequently, the amygdala [15], putamen [10,12-14,16], caudate nucleus [11,14-16], globus pallidus [11] and hippocampus [11,13-15] were also found to show atrophy in patients with temporal lobe epilepsy with or without MRI-visible hippocampal lesions. Thereafter, patients with IGEs, including absence epilepsy, juvenile myoclonic epilepsy (JME) and primary generalised tonic-clonic seizures, were also found to have subcortical abnormalities [3-10].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients with temporal lobe epilepsy (TLE) and idiopathic generalised epilepsy (IGE) have structural alterations in the subcortical nuclei and, more generally, in the thalamus [3-16]. Furthermore, the changes in subcortical GM correlate with the age at seizure onset and the duration of epilepsy [3,4,10,15,16]. A small number of longitudinal studies have shown that recurrent seizures may lead to progressive microstructural alterations [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread postictal diffusion changes around the seizure focus and remote areas (eg, thalamus and basal ganglia) have been shown in patients with focal and generalized epilepsy. 165,184,[198][199][200] Recurrent seizures, earlier age at seizure onset, and longer duration of epilepsy may also lead to microstructural changes along the seizure spread pathways. 167,172,199,201 Detecting Postoperative Changes Acute and chronic diffusion abnormalities, ipsilateral and contralateral to the epileptic focus, have also been seen after ATLR.…”
Section: Hs Resultsmentioning
confidence: 98%
“…in more extensive diffusion abnormalities involving ipsilateral and contralateral temporal neocortex and medial temporal structures, ipsilateral frontal lobe white matter, corpus callosum, basal ganglia, thalamus, and cerebellum. [163][164][165][166][167][168][169][170][171][172][173][174][175][176] Similarly, significant widespread diffusion abnormalities are found in the white matter tracts adjacent to and distant from lesions (eg, focal cortical dysplasia 177-179 ; in frontal lobes in children with drug-resistant focal epilepsy 180 ; in corticothalamic network in IGE and its subtypes, JME and childhood absence epilepsy [181][182][183][184][185][186] ). These widespread changes are not detected by conventional structural imaging and may reflect microstructural damage in a network distribution.…”
Section: Detecting Unseen Changes and Understanding The Mechanism Of mentioning
confidence: 99%